A formação continuada de professores que ensinam matemática na perspectiva da educação inclusiva: uma análise do “Ambiente Virtual de Formação” da rede municipal de ensino de Limeira-SP - Frei, Ligia Maria Salmazi (Universidade Federal de São Carlos, 2024)
This study addresses the issue of teacher training concerning the preparation to deal with the diversity of students who have different special educational needs and learning styles, particularly in the teaching of mathematics in the early years of elementary education. It discusses some of the main laws aimed at guaranteeing the rights of these students, covering both initial and continuing education, as both require a constant commitment to the professional development of teachers so that they can truly meet the demands of an inclusive classroom. The objective was to analyze the contributions of the training offered on the PerForme platform, a virtual environment for continuing education developed by the municipal network of Limeira-SP, aimed at supporting teachers in the teaching and learning of curriculum content. For this purpose, we identified which training programs related to mathematics and special education were most accessed, how many participants completed each stage, and how many effectively completed these trainings, creating tables based on the information obtained. Following this, we sent a questionnaire to the teachers and conducted in-person interviews with 8 participants. The theoretical framework of this study is based on authors with a critical approach, opting for both quantitative and qualitative treatment, as we understand that the numbers extracted from the PerForme platform cannot be adequately interpreted without considering their qualitative dimension, which encompasses educational policies, the complexity of teacher training, and the related historical context. Additionally, we recognize the dialectics of social relations that permeate this scenario, thus adopting an analysis grounded in Historical-Dialectical Materialism, which emphasizes the dynamic, contradictory, and historical nature of the phenomena studied. From the analysis and reflection on the collected data, we found that, despite the availability of training and high demand for certain content and deficiencies, teachers are unable to complete them due to the extensive workload and day-to-day demands. It was identified that when PerForme training sessions are completed, they are important and assist teachers in the classroom. It was also possible to detect a communication gap between the Municipal Department of Education and schools regarding the dissemination of the training offered by the platform, as well as the procedures for participation and the relevance of the certificates. The results indicate that it is necessary to promote public policies for teacher wellbeing, thus overcoming the institutional and political structures that perpetuate educational inequalities, promoting a more equitable and democratic education in teacher training.
Continuing training of teachers who teach mathematics from the perspective of inclusive education: an analysis of the network’s “Virtual Training Environment” municipal education of Limeira-SP
Keywords: Formação continuada; Ambiente virtual; Matemática inclusiva; Continuing education; Virtual environment; Inclusive mathematics; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL